Synthesis, Characterization and Biological Studies of New Schiff Bases and Azetidinones Derived from Propionic Acid Derivatives - Kumar Fuloria, Neeraj; Singh, Vijender; Shaharyar, Mohd.; Ali, Mohammad (Asian Journal of Chemistry, 2010)
Phenyl propionohydrazide (2), a hydrazinated derivative of methyl phenyl propanoate (1), when refluxed with aromatic aldehydes yielded Schiff bases 3A-E, which on subsequent cyclization with triethylamine and chloroacetylchloride yielded azetidinones 4A-E. The novel series of compounds were elucidated on the basis of spectral studies and screened for antibacterial and antifungal studies.